2012
DOI: 10.1523/jneurosci.2636-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphic Microsatellite Repeat within the ECE-1c Promoter Is Involved in Transcriptional Start Site Determination, Human Evolution, and Alzheimer's Disease

Abstract: Genetic factors strongly contribute to the pathogenesis of sporadic Alzheimer's disease (AD). Nevertheless, genome-wide association studies only yielded single nucleotide polymorphism loci of moderate importance. In contrast, microsatellite repeats are functionally less characterized structures within our genomes. Previous work has shown that endothelin-converting enzyme-1 (ECE-1) is able to reduce amyloid ␤ content. Here we demonstrate that a CpG-CA repeat within the human ECE-1c promoter is highly polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 66 publications
0
17
0
1
Order By: Relevance
“…Ece-1 function in the heart has been proposed to be important in the formation of the cardiac conduction system (Hall et al, 2004; Takebayashi-Suzuki et al, 2000). Four Ece-1 isoforms have been described (Schweizer et al, 1997; Valdenaire et al, 1999); the different ECE1 transcripts are initiated from distinct transcriptional start sites, which results in slight variations in the N-termini of the different proteins produced (Funke-Kaiser et al, 2000; Li et al, 2012; Orzechowski et al, 1997; Valdenaire et al, 1999). However, how ECE1 is controlled transcriptionally remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ece-1 function in the heart has been proposed to be important in the formation of the cardiac conduction system (Hall et al, 2004; Takebayashi-Suzuki et al, 2000). Four Ece-1 isoforms have been described (Schweizer et al, 1997; Valdenaire et al, 1999); the different ECE1 transcripts are initiated from distinct transcriptional start sites, which results in slight variations in the N-termini of the different proteins produced (Funke-Kaiser et al, 2000; Li et al, 2012; Orzechowski et al, 1997; Valdenaire et al, 1999). However, how ECE1 is controlled transcriptionally remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, how ECE1 is controlled transcriptionally remains incompletely understood. Some analyses of proximal promoter elements in cell culture-based studies have been described (Funke-Kaiser et al, 2000; Li et al, 2012; Orzechowski et al, 1998; Orzechowski et al, 1997; Valdenaire et al, 1999), but the regulation of the ECE1 gene in vivo has not been addressed previously.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Li et al demonstrated that CA repeats within the endothelin-converting enzyme-1 (ECE-1c) gene promoter are highly polymorphic and harbor transcriptional start sites and CA repeat length, indicating shifted allelic frequency distributions. These data indicate that genomic repeat composition constitutes a novel core promoter element and affects transcriptional start site determination (29).…”
Section: Discussionmentioning
confidence: 77%
“…A CpG-CA repeat within the human endothelin-converting enzyme-1 (ECE-1) promoter is highly polymorphic, harbours transcriptional start sites, it is able to recruit the transcription factors, poly(ADP)ribose polymerase-1 and splicing factors, it is functional regarding haplotype-specific promoter activity. Overall CpG-CA repeat composition of Alzheimer disease patients and controls is distinct [72]. A length polymorphism of GT repeats in the promoter region of the human heme oxygenase-1 (HO-1) gene modulates its gene transcription [73].…”
Section: Dna Secondary Structurementioning
confidence: 99%